2018
DOI: 10.18356/73d010ed-en
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and gender inequality: An analysis of panel data for five Latin American countries

Abstract: This study looks at the relationship between the feminization of the labour market-defined as a relative increase in the female labour force participation rate and in the female labour supply as measured in hours-and economic growth in five Latin American countries. On the one hand, these trends are reflected in the potential demand that labour force participation can channel into economic growth. On the other, the conditions under which women enter and remain in the labour market will determine their supply-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Second, Vásconez Rodríguez's research in Peru demonstrates that the enactment of gender mainstreaming policies in the labor market correlates to the country's GDP gain of 4. 7% in 2007(Vásconez Rodríguez, 2018. Third, Altuzarra et al (2021) discovered in their research that gender imbalance in the education sector impedes economic growth.…”
Section: Azis and Azarinementioning
confidence: 99%
“…Second, Vásconez Rodríguez's research in Peru demonstrates that the enactment of gender mainstreaming policies in the labor market correlates to the country's GDP gain of 4. 7% in 2007(Vásconez Rodríguez, 2018. Third, Altuzarra et al (2021) discovered in their research that gender imbalance in the education sector impedes economic growth.…”
Section: Azis and Azarinementioning
confidence: 99%
“…A growing literature documents the nexus between gender equality and economic output (Agénor & Canuto, 2015;Bertay et al, 2021;Eastin & Prakash, 2013;Kim et al, 2016;Klasen, 1999;Klasen & Lamanna, 2009;Mishra et al, 2020;Seguino, 2000;Vásconez Rodríguez, 2018). Klasen (2002) uses cross-country and panel regressions to examine the effect of gender inequality in education on longterm economic growth.…”
Section: Related Previous Studiesmentioning
confidence: 99%
“…In recent years, an increased number of studies have debated the link between gender inequality and economic growth (Vásconez Rodríguez, 2018). The main theory is that the elimination of gender disparities can create a faster and stronger growth engine for more resilient, sustainable, and inclusive economies, especially with equality in education and the labour market (IMF, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 2 , the total set of data table in our research comprised a sample of 932 observations, which indicated the suitability for adopting Panel Vector Auto-regression model. Besides, the above data summary table demonstrates that the standard deviation is smaller than the mean value, which is suitable for further data analysis [ 37 , 58 , 59 ].…”
Section: Datamentioning
confidence: 99%